PEMBERIAN KOMBINASI PUPUK HIJAU Azolla pinnata DENGAN PUPUK GUANO TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN PAKCHOY (Brassica chinensis L.) - OS, Ozi Nurhasanah; Yetti, Husna; Ariani, Erlida (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aimed to look the influence of the combination of green fertilizer Azolla pinnata with guano toward the growth and production of pakchoy and to obtain the best treatment from Azolla pinnata with guano toward pakchoy. This research was conducted at the experimental farm of Farming Faculty of Riau University. This research was accomplished during 3 months that was from June to August 2014. It was carried out experimentally with Group Random Design (GRD), the treatment given which consisted of several stages; P0 = without any treatment ( 0 kg/plot), P1 = Azolla 0,5 kg/plot + guano 0,3 kg/plot, P2 = Azolla 0,5 kg/plot + guano 0,4 kg/plot, P3 = Azolla 1 kg/plot + guano 0,3 kg/plot, P4 = Azolla 1 kg/plot + guano 0,3 kg/plot, P5 = Azolla 1,5 kg/plot + guano 0,3 kg/plot, P6 = Azolla 1,5 kg/plot + guano 0,4 kg/plot. Every treatment was repeated 3 times so that it was obtained 21 experiment units. Every experiment unit consisted of 36 plants and 3 of them was being sample. The observed parameters were that the tall of plants, the amount of leaves, the wide of leaves, the weight of plants and the weight of plants which were deserve to consume. The obtained data was analyzed statistically with analysis of varience and continued to Duncan’s New Multiple Range Test (DNMRT) at 5% degree. The fertilizing combination of 1,5 kg/plot Azolla Pinnata and 0,3 kg/plot guano was the best treatment in raise the growth and production of pakchoy. Keywords: Pakchoy, Azolla pinnata, Guano